The Development And Implementation Of A Creativity Module In Art Education Among Primary School Pupils In Saudi Arabia - Al-Ghamdi, Ahmed Ibrahim (2013)
The purpose of the study is to develop and implement creativity module. Five objectives of the study developed are to: 1) 17Tdevelop creativity module which incorporate artistic expression, 2) implement creativity module to facilitate creative abilities among Fifth Grade pupils, 3) identify the aspects and levels of creative abilities accomplished by Fifth Grade pupils, 4) find out the suitability of the creativity module based on teacher and pupils’ feedback, and 5) determine the role of Art Education teacher and pupils on the implementation of creativity module. 17TTheoretically, the study is based on Torrance’s Theory of Creativity (1974), Dickie’s Expression Theory of Art and Emotion (1997) and Herberholz & Hanson’s Artistic Expression (1985). This is a case study which employs qualitative research method. Observation checklist, interview and observation record were used to collect the data. The sample of the study consist eight pupils of the Fifth Grade in one of the government primary school in Al-Baha City, Kingdom of Saudi Arabia. Descriptive analysis was employed to analyze the data obtained. The results of the study indicate that 1) the creativity module was successfully developed and validated, 2) the creativity module implemented was able to facilitate pupils’ creative abilities, 3) the aspects and level of all four creative abilities (fluency, flexibility, originality, details) of the creativity module were identified as high level, 4) the creativity module was suitable according to the teacher and students’ feedback, 5) the role of Art teacher was very important and all pupils were interactive during implementation of creativity module. The implication of the study shows that the development and implementation of the module would help teacher to facilitate creative abilities among primary school pupils. The module can be as a guideline for Art Education teachers in Saudi Arabia. It also helps teachers to highlight the importance of Art Education to their pupils and motivate pupils to be creative. Furthermore, it helps the teachers who endeavor to reveal creative abilities in preparing their teaching materials.